2011
DOI: 10.1021/jp111528c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Aggregation and Fibril Formation from Bovine Serum Albumin

Abstract: We have investigated the fibrillation propensity of different conformational isomers of an archetypal, all α-helical protein, namely, bovine serum albumin (BSA), under different pH conditions and ionic strengths using fluorescence and circular dichroism (CD) spectroscopy. At low pH and higher protein concentration, the partially folded conformers associate to form oligomers that are converted into ordered amyloid-like fibrils when incubated at elevated temperature. We have elucidated the mechanism of fibril fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
150
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 75 publications
13
150
1
2
Order By: Relevance
“…In the case of BSA, we used an acidic pH range, as to be far away from the isoelectric point to observe morph aggregation process. The optimum pH was found to be at 3.02; interestingly, a recent study that focuses on characterization of BSA fibrillation mechanism has reported similar results: in the range of 1.6-10.5, pH 3 was found to be the best value [3].…”
Section: Discussionmentioning
confidence: 57%
“…In the case of BSA, we used an acidic pH range, as to be far away from the isoelectric point to observe morph aggregation process. The optimum pH was found to be at 3.02; interestingly, a recent study that focuses on characterization of BSA fibrillation mechanism has reported similar results: in the range of 1.6-10.5, pH 3 was found to be the best value [3].…”
Section: Discussionmentioning
confidence: 57%
“…Aggregation and Amyloid Formation by BSA-It was suggested previously that BSA could form amyloid fibrils at low pH and in the presence of high salt conditions (42,43). To further examine the conditions required for BSA amyloid formation, lyophilized BSA (Sigma) was dissolved in PBS, pH 7.4, with a concentration of 21 mg/ml, and the concentration was determined by UV absorption measurement at 280 nm, considering the molar absorptivity of BSA as 43,824 M Ϫ1 cm Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…The all-α-helical, 583-residue protein BSA ( Fig. 2A) was used for our initial studies as it has well-characterized intrinsic aggregation pathways (28)(29)(30) and its behavior under shear and extensional flow fields has been investigated previously (11,31). To assess whether our extensional flow device can induce protein aggregation, 500 μL gelfiltered monodisperse BSA (Methods) at a concentration of 1, 2, 5, or 10 mg mL −1 was passed through the capillary 500, 1,000, 1,500, or 2,000 times at a plunger velocity of 8 mm s −1 (equivalent to total exposure times to extensional flow of 9, 18, 27, and 36 ms, respectively, at fixed centerline strain-(11,750 s −1 ) and (C) TEM images of 5 mg mL −1 BSA after 0 (Top) and 2,000 passes (Bottom).…”
Section: Design and Computational Characterization Of Extensional Flowmentioning
confidence: 99%